Herzfrequenzvariabilität (HRV) und subjektives Belastungsempfinden (RPE) bei erschöpfender Ausdauerbelastung - Böselt, T.; Hoos, O. (Herzfrequenzvariabilität: Gesundheitsförderung - Trainingssteuerung - Biofeedback. Internationales Symposium am 29. und 30. Oktober., 2011)
Within the last few years complex models of cardiovascular regulation and exercise fatigue have been presented and have been associated with nonlinear measures of heart rate variability (HRV) and ratings of perceived exertion (RPE), respectively. Until now, both measures have only been used separately to analyse cardiovascular regulation during fatiguing exercise and no direct link between HRV and RPE has been shown. Therefore, the purpose of the current study was to analyze the relationship between linear and nonlinear parameters of HRV and ratings of perceived exertion (RPE) during exhaustive cycling exercise. n = 19 cyctists (age: 25,1 ± 3,8 years, weight: 77,3 ± 8,4 kg, VO²max: 55,4 ± 5,4 ml/(kg*min)) performed a submaximal constant load test until exhaustion with the power exerted at the individual anaerobic threshold (IANS) that was determined previously. Besides heart rate (HR) and standard time domain HRV measures of SDNN and RMSSD (in ms), the short- and long-term fractal scaling exponent alpha1 and alpha2 of the detrended fluctuation analysis (DFA) were calculated for every five minutes. Additionally, perceived exertion (RPE, CR-10), blood lactate and oxygen uptake (VO²) were assessed for every five minutes. All measures were interpolated to 10% steps of time to exhaustion. Repeated measures ANOVA was used to detect effects of exercise duration, while relations with RPE were assessed by pearson's correlation coefficient.